Precision measurement of the [xi]cc mass - Aaij, Roel; Ackernley, T.; Archilli, Flavio; Beteta, C. Abellán; Borsato, Martino; Braun, Svende; Comerma-Montells, Albert; D'Argent, Philippe; Dziewiecki, Michal; Gerick, David; Grabowski, Jascha; Han, Xiaoxue; et al. (Journal of high energy physics, 2020)
A measurement of the Ξcc++$$ {\varXi}_{cc}^{++} $$ mass is performed using data collected by the LHCb experiment between 2016 and 2018 in pp collisions at a centre-of-mass energy of 13 TeV, corresponding to an integrated luminosity of 5.6 fb−1. The Ξcc++$$ {\varXi}_{cc}^{++} $$ candidates are reconstructed via the decay modes Ξcc++→Λc+K−π+π+$$ {\varXi}_{cc}^{++}→ {\varLambda}_c^{+}{K}^{-}{π}^{+}{π}^{+} $$ and Ξcc++→Ξc+π+$$ {\varXi}_{cc}^{++}→ {\varXi}_c^{+}{π}^{+} $$. The result, 3621.55 ± 0.23 (stat) ± 0.30 (syst) MeV/c2, is the most precise measurement of the Ξcc++$$ {\varXi}_{cc}^{++} $$ mass to date.
The LHCb Collaboration: R. Aaij, F. Archilli, S. Bachmann, D. Berninghoff, M. Borsato, S. Braun, M. De Cian, F. Dordei, D. Gerick, J.P. Grabowski, X. Han, S. Hansmann-Menzemer, J. Hu, R. Kopecna, B. Leverington, H. Malygina, J. Marks, A. Piucci, U. Uwer, L. Witola, A. Zhelezov [und weitere]
Artikel Nr. 49
Im Titel sind die Plus-Zeichen hochgestellt
Im Titel ist "Xi" als griechischer Buchstabe dargestellt
"cc" im Titel ist tiefgestellt